AN ATTEMPT TO UNDERSTAND ROOT CAUSE BEHIND HIGH LEVELS OF LEAD CONTENT IN “MAGGI” - Shrivastava, Sudha; Yadav, Sarita (International Journal of Research -GRANTHAALAYAH, 2015)
Maggi Noodles by Nestle are banned and taken off shelves in India because of the high lead levels in the product. In my opinion, Nestle is not deliberately increasing the lead content, but lead content can be found in greater than expected quantity due to increase in lead content in its raw materials. One may read all the ingredients of the Maggi noodles as we as its taste enhancer mentioned on the wrapper of the product. What can be the cause of presence of lead, what can be its source and how does it affect human health? Lead is present in all sections of our environment. Air, Soil, Water, every element of environment contains lead. Lead and lead compounds have been used under wide variety of products found in and around our houses, and now as per reports, even the most handy food product called Maggi noodles has lead, more than acceptable to human health. As we are aware, lead is a naturally occurring element found in small amount in the earth’s crust. While it has some beneficial uses, it can be toxic to human and animals causing health issues.